The Contribution of the Majelis Zikir and Sholawat Khoirun Dakwah in Enhancing the Spirit of Spirituality among the Residents of Kerpangan, Leces, Probolinggo. - Fika Maghfiroh; Abu Yazid Adnan Quthny; Bahruddin Zaini (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2023)
Along with the development of the Western world's influence on fashion, fun, and food, many residents of Kerpangan Village consider the benchmark of perfection based on Western trends. This has led to neglecting their religious obligations, such as reduced time for remembrance (zikir), decreased time for voluntary prayers (salat sunnah), and so on. Not only that, but the attitude of the residents has also deteriorated. Eventually, Habib Ahmad Zakiq Al-Hasni came up with a brilliant idea to establish the Majelis Zikir and Sholawat Khoirun Dakwah as a means to bring the residents closer to the Creator through guided recitation led by Habib Zaky himself. The main objective of this research is to identify the various activities organized by the Majelis Zikir and Sholawat Khoirun Dakwah and to understand the strategies used to enhance the spirit of spirituality among the residents of Kerpangan Village. The researcher employed interview, observation, and documentation methods. Interviews were conducted with the founder of Majelis Khoirun Dakwah, Habib Zaky, several loyal followers of the Majelis Zikir, and also with a local community leader. The results of this research show that all activities of the Majelis Zikir and Sholawat Khoirun Dakwah have a positive impact and are warmly welcomed by the residents. The strategies used by the Majelis Zikir and Sholawat Khoirun Dakwah include direct da'wah by attending Majelis Zikir and Sholawat Khoirun Dakwah events, as well as indirect da'wah through social media platforms such as YouTube.